Improving Elementary School Students’ Wudu Ablution Skills With The Use of Images and Audio-Visual Props - Sa'duh, Septria; Firmansyah , Mhd. Zidan; Makruf, Makruf; Sabri, Ahmad; Hidayatullah, Rully (Journal of Regional Development and Technology Initiatives, 2024)
This research aims to evaluate the ablution proficiency of second-grade students at 24 Biaro State Elementary School during the academic year 2023/2024 and to explore the effectiveness of using visual and audio-visual media in enhancing this skill. Previously, ablution instruction at this school primarily relied on lecture-based methods that often failed to actively engage students, resulting in suboptimal learning outcomes. However, with the introduction of visual and audio-visual aids as a new innovation in ablution instruction, the learning environment has become more stimulating and interactive. The use of these media provides students with the opportunity to actively participate in the learning process. They can clearly observe the correct sequence and techniques for performing ablution, both in physical movements and in reciting relevant verses. The importance of accurate pronunciation in ablution recitations is also emphasized, prompting the researcher to adopt a method of reciting the verses aloud to swiftly detect and correct pronunciation errors. Data collected from this study were analyzed using descriptive statistical techniques. The results indicate a significant improvement in ablution proficiency when visual and audio-visual media are employed in instruction. Comparisons of students' practical test results from pre-cycle to cycle II show consistent improvement, with the highest scores achieved in cycle II. This confirms the hypothesis that the use of visual and audio-visual aids can enhance ablution proficiency among second-grade students at 24 Biaro State Elementary School.